Beyond Rote Memorization: Reconstructing Quranic Pedagogical Frameworks Through Neurocognitive Learning Principles in Indonesian Islamic Schools - Rasmuin, Rasmuin; Khasani, Fahim (Journal of Education Method and Learning Strategy, 2026)
This article addresses a gap between Islamic educational philosophy and contemporary learning science: the absence of a theoretically grounded framework that reconciles the ḥifẓ (Quranic memorization) tradition with neurocognitive evidence on deep, durable learning. Quranic memorization has long served as the epistemological foundation of Islamic scholarly transmission in Indonesia and the wider Muslim world. However, its dominant pedagogical form—mechanical repetition-based rote learning—has increasingly been identified as cognitively suboptimal and poorly aligned with how the human brain encodes and retains complex knowledge over time. Existing scholarship tends to take two opposing positions. Some defend memorization through theological arguments without engaging cognitive science, while others critique it through secular constructivist frameworks that overlook the spiritual and epistemic dimensions of Quranic pedagogy. Using qualitative conceptual library research and interdisciplinary thematic synthesis, this article brings Islamic pedagogical traditions into dialogue with neurocognitive learning theories. It focuses particularly on the concepts of tartīl, tadabbur, and tarbiyah, and relates them to theories such as cognitive load theory, retrieval practice, spaced repetition, neuroplasticity, and embodied cognition. The analysis yields a novel conceptual model: the Neurocognitive Quranic Pedagogy (NQP) Framework, which proposes a reconstructed pedagogy that preserves the spiritual and epistemic integrity of ḥifẓ while substantially deepening its cognitive architecture. The article contributes to global debates on religious memorization pedagogy and offers actionable implications for Islamic school curriculum reform, teacher education, and knowledge transmission practices in Indonesia and beyond.